Review of enablers and barriers of sustainable business practices in SMEs - Shoaib Abdul Basit; Behrooz Gharleghi; Khadija Batool; Sohaib S. Hassan; Asghar Afshar Jahanshahi; Mujde Erdinc Kliem (Journal of Economy and Technology)
There are many factors that persuade or discourage business owners or managers of small and medium-sized firms to adopt sustainable policies. It is important to understand how different factors are interlinked to influence the business owners’/managers’ decisions for sustainability. Therefore, the gap between policies and their implementation in the workplace causes the failure of the adoption of sustainable policies in business practices. To provide a clear picture, the present study intends to investigate the factors that might foster/hinder the adoption of sustainable policies in business practices. The study provides a systematic literature review on sustainable business policies from 2015 to 2023. We consider what are the key factors supporting or obstructing the successful implementation of a sustainability framework in the business practices in SMEs. Our findings reveal that data-centered solutions, sensor aided cyber physical systems, green consumption, vendor support, technological roadmap, gain legitimacy on the use of data analytics, and acceleration of digital transformation are the most significant enablers for sustainable business practices in SMEs. In addition, cloud enterprise resource planning is found to be the most significant enabler for developing countries. The barriers are mainly related to the implantation of the enablers. Among those major barriers are security of the data storage, lack of trust, lack of top management support, resistance to change to the new technology, lack of skilled workforce, data breaches, and poor network security. Our findings have key policy implications for practitioners and policy makers.